Community social psychology: rethinking the discipline from the community stand point - Sánchez, euclides (Revista de Psicología, 2001)
The criticisms of traditional social psychology and the uprise of alternative paradigms in the social sciences, has stimulated the development of a new social psychology, particularly of the community social psychology (CSP). CSP’ research agenda, however, is not clear in relation to the extent of the participation of civil society and specifically of the community in the construction of such agenda. This project demands tasks such as determining the conception of issues or problems to be studied, the methodology to be employed for researching community problems, the benefits of this research for the community or the analysis of the community social psychologist-community relationship.In this paper and based on interviews with members of communities of different socioeconomic level, a set of considerations for the development of a new program for CSP are made.